2014
DOI: 10.1038/ncomms5992
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Wnt signalling triggers striatal synaptic degeneration and impaired motor behaviour in adult mice

Abstract: Synapse degeneration is an early and invariant feature of neurodegenerative diseases. Indeed, synapse loss occurs prior to neuronal degeneration and correlates with the symptom severity of these diseases. However, the molecular mechanisms that trigger synaptic loss remain poorly understood. Here we demonstrate that deficient Wnt signalling elicits synaptic degeneration in the adult striatum. Inducible expression of the secreted Wnt antagonist Dickkopf1 (Dkk1) in adult mice (iDkk1) decreases the number of corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
94
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(103 citation statements)
references
References 55 publications
(108 reference statements)
9
94
0
Order By: Relevance
“…Thus, we speculate that decreased glial activation and enhanced NSC and DAergic neuronal survival observed in our study could be due to decreased GSK-3β activation and increased β-catenin stabilization, indicating a role of ALCARmediated regulation of the Wnt/β-catenin pathway. Earlier studies suggested that the Wnt/β-catenin pathway stimulates selfrenewal of NSC and differentiation [55] towards neuronal phenotype by inhibiting gliogenesis [56], and down-regulation of this pathway causes striatal synaptic degeneration, resulting in impaired motor behaviour [57].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we speculate that decreased glial activation and enhanced NSC and DAergic neuronal survival observed in our study could be due to decreased GSK-3β activation and increased β-catenin stabilization, indicating a role of ALCARmediated regulation of the Wnt/β-catenin pathway. Earlier studies suggested that the Wnt/β-catenin pathway stimulates selfrenewal of NSC and differentiation [55] towards neuronal phenotype by inhibiting gliogenesis [56], and down-regulation of this pathway causes striatal synaptic degeneration, resulting in impaired motor behaviour [57].…”
Section: Discussionmentioning
confidence: 99%
“…That these classic developmental cues may have critical functions in the adult brain has been implied by recent findings that broad-spectrum blockade or activation of Wnt pathway components affects synaptic structure, plasticity, and cognitive functions in adult animals (37)(38)(39)(40)(41). However, surprisingly little is known about which of the 19 vertebrate Wnts is essential for adult nervous system functions in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, broad-spectrum Wnt antagonists have been shown to affect synaptic structure, plasticity, and cognitive functions in adult organisms (37)(38)(39)(40)(41). However, there are 19 vertebrate Wnts, and which Wnt is essential for these functions in the adult brain in vivo remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…In rodents atrazine has been shown to alter locomotor activity (Bardullas et al, 2011; Belloni et al, 2011; Peruzovic et al, 1995; Rodriguez et al, 2013; Ugazio et al, 1991), delay righting reflexes (Belloni et al, 2011), and impair rotarod performance (Bardullas et al, 2011). These tasks have all been shown to measure behaviors that are controlled, in part, by NSDA neurons (Adeosun et al, 2012; Galli et al, 2014; Kravitz et al, 2010; Liu et al, 2014; Verhave et al, 2009; Yin et al, 2009). The walking beam assay assesses the ability of rats to traverse a narrow elevated beam and has proven to be very useful in the assessment of motor coordination (Goldsten, 2003).…”
Section: Introductionmentioning
confidence: 99%